Evaluating complex interventions in international development - Masset, Edoardo; Shrestha, S.; Juden, M. (CEDIL, 2021)
This paper reviews promising methods for the evaluation of complex int erventions that are new or have been used in a limited way. It offers a taxonomy of complex interventions in international development and d raws on literature to discuss several methods that can be used to eval uate these interventions. Complex interventions are those that are cha racterised by multiple components, multiple stakeholders, or multiple target populations. They may also be interventions that incorporate mu ltiple processes of behavioural change. While such interventions are v ery common and receive a large proportion of development aid budgets, they are rarely subject to rigorous evaluations. The CEDIL Methods Wor king Paper, ‘Evaluating Complex Interventions in International Develop ment’, reviews promising methods for the evaluation of complex interve ntions that are new or have been used in a limited way. It offers a ta xonomy of complex interventions in international development and draws on literature to discuss several methods that can be used to evaluate these interventions. The paper focuses its attention on methods that address causality and allow us to state conclusively whether an interv ention works or not. It shows that several rigorous methods developed in different disciplines can be adapted and used to evaluate complex i nterventions in international development.